Ecological Stoichiometry: A Link Between Developmental Speed and Physiological Stress in an Omnivorous Insect - Trakimas, Giedrius; Krams, Ronalds; Krama, Tatjana; Kortet, Raine; Haque, Shahi; Luoto, Severi; Eichler Inwood, Sarah; Butler, David M.; Jõers, Priit; Hawlena, Dror; Rantala, Markus J.; Elferts, Didzis; et al. (Frontiers in Behavioral Neuroscience, 2019)
The elemental composition of organisms is a part of a suite of functional traits that may adaptively respond to fluctuating selection pressures. Life history theory predicts that predation risk and resource limitations impose selection pressures on organisms’ developmental time and are further associated with variability in energetic and behavioral traits. Between-individual differences in developmental speed, behaviors and physiology have been explained using the pace-of-life syndrome (POLS) hypothesis. However, how an organism’s developmental speed is linked with elemental body composition, metabolism and behavior is not well understood. We compared elemental body composition, latency to resume activity and resting metabolic rate (RMR) of western stutter-trilling crickets (Gryllus integer) in three selection lines that differ in developmental speed. We found that slowly developing crickets had significantly higher body carbon, lower body nitrogen and higher carbon-to-nitrogen ratio than rapidly developing crickets. Slowly developing crickets had significantly higher RMR than rapidly developing crickets. Male crickets had higher RMR than females. Slowly developing crickets resumed activity faster in an unfamiliar relative to a familiar environment. The rapidly developing crickets did the opposite. The results highlight the tight association between life history, physiology and behavior. This study indicates that traditional methods used in POLS research should be complemented by those used in ecological stoichiometry, resulting in a synthetic approach that potentially advances the whole field of behavioral and physiological ecology.